Abyssinia's Samuel Johnson Ethiopian thought in the making of an English author - Belcher, Whitney (New York ; Oxford : Oxford University Press, 2012)
This title uncovers African influences on the Western imagination during the 18th century, paying particular attention to the ways Ethiopia inspired and shaped the work of Samuel Johnson.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Johnson, Samuel, -- 1709-1784 -- Sources; Johnson, Samuel, -- 1709-1784 -- Knowledge -- Ethiopia; English literature -- African influences; d; Johnson, Samuel, -- 1709-1784.; Johnson, Samuel, -- 1709-1784.; Ethiopia -- Civilization